Toward supramolecular nanozymes for the photocatalytic activation of Pt(iv) anticancer prodrugs. Issue 72 (2nd September 2020) - Mazzei, Laura F.; Martínez, Álvaro; Trevisan, Lucia; Rosa-Gastaldo, Daniele; Cortajarena, Aitziber L.; Mancin, Fabrizio; Salassa, Luca
Abstract : Nanozymes based on TACN AuNPs and FMN photocatalyze the activation of a Pt(iv ) prodrug into cisplatin. Abstract : A supramolecular nanozyme for the photocatalytic conversion of a Pt(iv ) anticancer complex to cisplatin is described herein. We employed 1.9 nm Au nanoparticles decorated with thiol ligands bearing a TACN (1, 4, 7-triazacyclononane) headgroup to encapsulate FMN (riboflavin-5′-phosphate). In the presence of an electron donor, flavin-loaded nanoparticles photocatalyzed the reductive activation of the prodrug cis, cis, trans -[Pt(NH3 )2 (Cl2 )(O2 CCH2 CH2 COOH)2 ] to cisplatin, achieving turnover frequency values of 7.4 min −1 .